BUSINESS MODEL TRANSFORMATION OF UKRAINIAN GRAIN TRADERS AS A KEY TO ENHANCING THEIR COMPETITIVENESS - FYLIUK, Halyna; MAGOMEDOVA, Alina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The current state and operational dynamics of Ukrainian grain trading companies have been assessed under the conditions of profound geopolitical and economic disruptions caused by the full-scale military aggression launched by Russian forces. Quantitative data reflecting the dynamics of active business entities engaged in wholesale grain trade have been analyzed. Key market entities have been identified, and the principal challenges to their competitiveness have been defined. A strong dependence of market performance on the geopolitical context has been revealed, with a marked decline observed in 2022 due to the destruction of logistical routes, the loss of production infrastructure, and a general economic downturn. Particularly, the volatility and decline in profit margins, the high reliance on raw commodity exports, the increase in indirect costs, a deepening labor shortage, the impact of climate change, and significant logistical constraints are identified as crucial problems for grain traders. It has been determined that, despite wartime conditions, the potential for the recovery of export activity remains, although it is conditional upon the transformation of grain traders’ business models. The necessity of shifting from the export of unprocessed grain to value-added production and the implementation of seasonal sales diversification has been justified. The elevator infrastructure in Ukraine has been examined, and its potential role in the process of business model transformation has been analyzed. The importance of this infrastructure in shaping pricing policies and improving operational efficiency has been outlined. The strategic adaptation of the grain trading sector to new operational realities has been identified as a prerequisite for enhancing its competitiveness in the global food market.